Stevenia gilasiani sp. nov. (Diptera: Rhinophoridae): the first woodlouse fly with male sexual-patches - Gisondi, Silvia; Lenzi, Alice; Ziegler, Joachim; Giulio, Andrea Di; Cerretti, Pierfilippo (Zootaxa, 2019)
Stevenia gilasiani Ziegler, Gisondi & Cerretti, sp. nov. from western Iran is described and illustrated. Cladistic arguments are provided in order to give an explicit genus level affiliation for the new species. Stevenia gilasiani sp. nov. is the first rhinophorid characterized by male ventral sexual-patches on abdominal tergites 3, 4 and 5 and sternites 3 and 4, and is the only Stevenia characterized by two postpronotal setae instead of usual three. A comparison with all congeners is made.